Method for constructing food-grade Janus liquid drops with adjustable particle sizes based on multiphase spatial recombination

By regulating the flow behavior of zein and sodium alginate in a microfluidic chip, forming a laminar flow state and under the shearing of the oil phase, food-grade Janus droplets with uniform particle size distribution were successfully constructed, solving the problem of difficult interface balance in the prior art, and improving the stability and product quality of the droplets.

CN119856775APending Publication Date: 2025-04-22OCEAN UNIV OF CHINA

Patent Information

Application Number
CN202510125921.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively construct food-grade Janus droplets with uniform particle size distribution, especially under the influence of proteins and polysaccharides, and the interface balance between the three phases is difficult to control.

Method used

By leveraging the discrete phase separation phenomenon of zein and sodium alginate, the flow behavior of the two phases is regulated in the microfluidic chip to form a laminar flow state, and food-grade Janus droplets with uniform particle size distribution are formed under the shearing action of the oil phase.

Benefits of technology

The uniform particle size distribution of food-grade Janus droplets is achieved, the stability of the droplets and the bioavailability of the active substances are improved, and the consistency of product quality is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119856775A_ABST
    Figure CN119856775A_ABST
Patent Text Reader

Abstract

The invention discloses a method for constructing food-grade Janus liquid drops with adjustable particle sizes based on multiphase spatial recombination, and belongs to the technical field of liquid drop preparation. According to the preparation method, space phase behaviors of a zein solution and a sodium alginate solution are controlled, the zein solution and the sodium alginate solution which are incompatible with each other are taken as a dispersion phase, and an emulsifier is dissolved in an oil phase to serve as a continuous phase. The laminar behavior of the zein solution and the sodium alginate solution is controlled, and the food-grade Janus liquid drops are prepared under the shearing action of a continuous phase. A series of food-grade Janus liquid drops with controllable particle sizes are constructed by controlling the molecular weight of sodium alginate, the concentration of a dispersed phase, the concentration of an emulsifier, three-phase interface equilibrium and three-phase flow velocity. According to the method for constructing the food-grade Janus liquid drops, the Janus liquid drops which are uniform in particle size and stable in structure can be constructed, and meanwhile, the material for constructing the Janus liquid drops has good biocompatibility and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of droplet preparation, and in particular relates to a method for constructing food-grade Janus droplets with adjustable particle size based on multiphase spatial recombination. Background Art

[0002] Janus droplets are composed of two incompatible liquid phases, which can realize the loading of multiple substances and the integration of multiple functions. They have played an important role in the fields of chemistry, materials and medicine, and can meet complex application requirements. However, existing Janus droplets are usually composed of synthetic polymer materials, and their application in the food field is limited due to their poor safety. Proteins, polysaccharides and edible oils are common food-grade materials and are good raw materials for constructing food-grade droplets. With the deepening of scientific research, discrete phase separation has been found in protein and polysaccharide solutions. This is mainly due to the difference in the conformation of the two. At high concentrations, the two will undergo discrete phase separation and show incompatibility, which provides a good foundation for the construction of food-grade Janus droplets. However, the interfacial balance between the three phases has an important influence on the asymmetric conformation of Janus droplets. Since proteins and polysaccharides in food can significantly affect the interfacial tension, thereby affecting the interfacial balance between the three phases, and ultimately destroying the Janus conformation of the droplets, proteins and polysaccharides can significantly affect the construction of food-grade Janus droplets. How to effectively control the spatial behavior of the three phases to construct food-grade Janus droplets still faces great challenges. Given the huge application prospects of Janus droplets in the food field, it is necessary to develop a method to construct food-grade Janus droplets.

[0003] As shown in the following patent: Application number: CN202410320827.4, Publication number: CN118271873A, Invention name: "A method for preparing color-adjustable total internal reflection structural color droplets", a method for preparing Janus droplets is disclosed. This method can be used to prepare Janus droplets, but Janus droplets are composed of hydrocarbons and fluorocarbons, and their safety cannot meet the application requirements in food.

[0004] As shown in the following patent: Application number: CN202310923464.9, Publication number: CN117050031A, the invention name is "Fluorothiazolidinone and its synthesis method", which discloses a method for preparing Janus droplets. This method constructs Janus droplets based on vortex oscillation emulsification or shear emulsification technology, but because the vortex or shear process cannot be well controlled, the uneven energy input leads to uneven particle size of Janus droplets, which may affect its performance in subsequent applications. In addition, Janus droplets are composed of perfluorooctane and n-hexane, both of which are toxic and cannot be used in food.

[0005] The article "Destabilization mechanism of (W1+W2) / O reverse Janus emulsions" discloses a technique for constructing Janus droplets. This method constructs Janus droplets based on an incompatible salt-alcohol system (sodium carbonate and ethanol) by a vortex method. However, the ethanol in the Janus droplets may not be conducive to their application in food. In addition, the Janus droplets constructed by the vortex method have a wide range of particle sizes, which may affect their subsequent applications.

[0006] As mentioned above, there is still a lack of a method for constructing food-grade Janus droplets with uniform particle size distribution. At present, there is no report on the method of constructing food-grade Janus droplets with uniform particle size distribution by proteins and polysaccharides. Summary of the invention

[0007] The main purpose of the present invention is to provide a method for constructing food-grade Janus droplets with adjustable particle size based on multiphase spatial recombination, and to prepare food-grade Janus droplets, so as to overcome the shortcomings of the prior art.

[0008] The principle of the present invention is based on the spatial phase behavior of zein and sodium alginate under different conditions, using the key point of discrete phase separation of zein solution and sodium alginate solution, and using the two phases as mutually incompatible dispersed phases to construct food-grade Janus droplets. At the same time, by regulating the flow behavior of the two phases in the microfluidic chip, the two phases are placed in a laminar state. The laminar flow forms a "contraction cone" under the dual effects of the geometric structure constraint and the continuous phase pressure. In the process of three-phase flow, the continuous pressure will cause the liquid at the front end of the "contraction cone" to be completely unstable, and finally form food-grade Janus droplets with uniform particle size distribution.

[0009] In order to achieve the technical purpose of the present invention, the technical solution of the present invention includes the following steps: (1) dispersing sodium alginate in deionized water, stirring and dissolving, homogenizing, and adjusting the pH of the solution to obtain a sodium alginate solution as one of the dispersed phases; (2) dispersing zein in deionized water, stirring and dissolving, homogenizing, and adjusting the pH of the solution to obtain a zein solution as one of the dispersed phases; (3) dissolving the emulsifier in the oil phase to obtain a continuous phase solution; (4) Food-grade Janus droplets were constructed by controlling the flow rates of zein solution, sodium alginate solution, and oil phase, respectively.

[0010] Preferably, the molecular weight of the sodium alginate in step (1) is 50 kDa; Preferably, in step (1), the concentration of the sodium alginate solution is 2 wt %, and the pH of the solution is 12.0; Preferably, in step (2), the concentration of zein is 12 wt %, and the pH of the solution is 12.0; Preferably, in steps (1) and (2), the homogenization method is ultrasound; Preferably, in step (3), the emulsifiers are PGPR and lecithin; Preferably, in step (3), the emulsifier concentration is 2 wt %; Preferably, in step (3), the oil phase is medium chain triglycerides; Preferably, in step (4), the flow rate of the zein solution is 1.2 μL / min; the flow rate of the sodium alginate solution is 0.6 μL / min; and the flow rate of the oil phase is 1.0 μL / min.

[0011] Compared with the prior art, the present invention has the following beneficial effects: (1) The zein, sodium alginate, PGPR and oil phase used in the present invention are all food-grade raw materials, and the food-grade Janus droplets constructed on this basis have good safety.

[0012] (2) The present invention fully coordinates the influence of the dispersed phase concentration change on the phase separation behavior, flow behavior and interface equilibrium, and constructs food-grade Janus droplets by utilizing the balance among multiple factors.

[0013] (3) The zein and sodium alginate selected in the present invention have certain interfacial activity and can interact with the emulsifier, thereby enhancing the stability of the food-grade Janus droplets.

[0014] (4) The present invention adopts homogenization treatment when preparing zein and sodium alginate solution, including high-speed shearing, ultrasound and high-pressure homogenization. Such treatment method can make zein or sodium alginate dissolve better in the solution, reduce the aggregation and precipitation of substances, and thus improve the stability of the solution. Homogenization treatment can also reduce the difference in properties between different batches of raw materials, thereby making the preparation conditions of food-grade Janus droplets more stable, which is beneficial to the quality control of food-grade Janus droplets.

[0015] (5) The present invention has good control over the flow of zein solution, sodium alginate solution and oil phase in the microfluidic chip channel. Due to the difference in fluid properties, the flow of zein solution, sodium alginate solution and oil phase in micrometer-scale space is significantly different. Through the fine control of their flow behavior, the laminar flow of zein solution and sodium alginate solution in the chip channel is achieved, and finally food-grade Janus droplets are formed under the shearing action of the oil phase.

[0016] (6) The food-grade Janus droplets constructed by the present invention have a uniform particle size distribution, which can effectively improve the stability of the droplets and provide more consistent bioavailability of the active substance. The uniform particle size can also reduce the differences between different batches of products, which is beneficial to improving product quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of constructing food-grade Janus droplets according to the present invention.

[0018] Figure 2 This is an appearance diagram of the discrete phase separation of the zein solution and the sodium alginate solution in Example 1.

[0019] Figure 3 This is a fluorescence microscope image of the discrete phase separation of zein and sodium alginate in Example 1.

[0020] Figure 4 Microscopic image of the fluid structure produced during the construction of food-grade Janus droplets in Example 2.

[0021] Figure 5 This is a microscopic image of a single-phase droplet.

[0022] Figure 6 This is a microscopic image of the food-grade Janus droplets prepared in Example 1.

[0023] Figure 7 This is the particle size distribution diagram of the food-grade Janus droplets prepared in Example 1.

[0024] Figure 8 The effect of flow rate on the particle size of food-grade Janus droplets.

[0025] Fig. 9 TSI values ​​for food grade Janus droplets.

[0026] Fig.10 Thermal stability of food-grade Janus droplets.

[0027] DETAILED DESCRIPTION OF THE EMBODIMENTS The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0028] Operations not mentioned in the present invention are all routine operations in the art, and materials whose specific sources are not mentioned in the present invention are all conventional materials that can be purchased from the market.

[0029] Example 1 Sodium alginate with a molecular weight of 50 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 12 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR and lecithin were dissolved in medium-chain triglycerides (MCT) at a ratio of 1:1, and the emulsifier concentration was 2 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1 μL / min, respectively. The sodium alginate phase and the zein phase formed a laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0030] Example 2 Sodium alginate with a molecular weight of 50 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 12 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR and lecithin were dissolved in MCT at a ratio of 1:1, and the emulsifier concentration was 2 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 2 μL / min, and the sodium alginate phase and zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0031] Example 3 Sodium alginate with a molecular weight of 50 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 12 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR and lecithin were dissolved in MCT at a ratio of 1:1, and the emulsifier concentration was 2 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow at flow rates of 0.6 μL / min, 1.2 μL / min and 3 μL / min in the microfluidic chip, and the sodium alginate phase and zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0032] Example 4 Sodium alginate with a molecular weight of 50 kDa was dispersed in deionized water to prepare a 1.5 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR was dissolved in MCT with a PGPR concentration of 2 wt% as a continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1.5 μL / min, respectively. The sodium alginate phase and the zein phase formed a laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0033] Example 5 Sodium alginate with a molecular weight of 10 kDa was dispersed in deionized water to prepare a 1.5 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR was dissolved in MCT with a PGPR concentration of 2 wt% as a continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1.5 μL / min, and the sodium alginate phase and the zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0034] Example 6 Sodium alginate with a molecular weight of 80 kDa was dispersed in deionized water to prepare a 1.5 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR was dissolved in MCT with a PGPR concentration of 2 wt% as a continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1.5 μL / min, respectively. The sodium alginate phase and the zein phase formed a laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0035] Example 7 Sodium alginate with a molecular weight of 10 kDa was dispersed in deionized water to prepare a 1.5 wt% solution, which was stirred and dissolved, and then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, and then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR and lecithin were dissolved in corn oil at a ratio of 1:1, and the emulsifier concentration was 2 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow at flow rates of 0.6 μL / min, 1.2 μL / min and 1 μL / min in the microfluidic chip, and the sodium alginate phase and zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0036] Example 8 Sodium alginate with a molecular weight of 10 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, and then subjected to high-pressure homogenization. The pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, and then subjected to high-pressure homogenization. The pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. Lecithin was dissolved in soybean oil with an emulsifier concentration of 2 wt% as a continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1 μL / min, respectively. The sodium alginate phase and the zein phase formed a laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0037] Example 9 Sodium alginate with a molecular weight of 10 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, and then subjected to high-speed shear treatment, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, and then subjected to high-speed shear treatment, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR and lecithin were dissolved in rapeseed oil at a ratio of 1:2, and the emulsifier concentration was 1.5 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1 μL / min, respectively. The sodium alginate phase and the zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0038] Example 10 Sodium alginate with a molecular weight of 10 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR was dissolved in corn oil with a PGPR concentration of 1 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow at flow rates of 0.6 μL / min, 1.2 μL / min and 1 μL / min in the microfluidic chip, and the sodium alginate phase and zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0039] Embodiment 11 Sodium alginate with a molecular weight of 10 kDa was dispersed in deionized water to prepare a 2 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a sodium alginate solution as one of the dispersed phases. Zein was dispersed in deionized water to prepare a 10 wt% solution, which was stirred and dissolved, then ultrasonically treated, and its pH value was adjusted to 12.0 to obtain a zein solution as one of the dispersed phases. PGPR was dissolved in the oil phase with a PGPR concentration of 3 wt% as the continuous phase. The sodium alginate solution, zein solution and oil phase were controlled to flow in the microfluidic chip at flow rates of 0.6 μL / min, 1.2 μL / min and 1 μL / min, and the sodium alginate phase and the zein phase formed laminar flow through the "Y" structure, and food-grade Janus droplets were formed under the shear of the oil phase.

[0040] Experimental Example 1 Observation of discrete phase separation behavior The zein solution and sodium alginate solution prepared in Example 1 were placed in a glass sample bottle, and the states of the two were observed. Zein was labeled with rhodamine B, and the zein solution and sodium alginate solution were mixed and observed under a fluorescence microscope.

[0041] pass Figure 2 It can be seen from the appearance of the zein solution and the sodium alginate solution that there is a discrete phase separation phenomenon. Figure 3 It can also be seen from the fluorescence microscope image that the zein solution forms spherical droplets in the sodium alginate solution, which also confirms the existence of discrete phase separation between the zein solution and the sodium alginate solution.

[0042] Experimental Example 2 Observation of three-phase flow behavior The microfluidic chip in Example 1 was placed under a microscope to observe the flow behaviors of the three phases.

[0043] pass Figure 4 The experimental results show that the zein solution and sodium alginate solution show laminar flow in the channels of the microfluidic chip, and there is an obvious interface between the two phases, proving the fact that the two phases are incompatible with each other. In addition, under the coordination of the pressure of the MCT phase and the channel structure, a "fluid cone" is formed at the end of the two phases, and the pressure of the MCT solution causes the liquid at the front end of the "fluid cone" to completely destabilize and form droplets.

[0044] Experimental Example 3 Microscope Observation of Single-Phase Droplets Single-phase droplets were prepared and observed under a microscope.

[0045] pass Figure 5It can be seen from the experimental results that the single-phase droplets are composed of a uniform dispersed phase, and no phase separation and interface can be observed in the droplets.

[0046] Experimental Example 4 Observation of Microstructure of Food-Grade Janus Droplets The food-grade Janus droplets prepared in Example 2 were placed under an optical microscope for observation.

[0047] pass Figure 6 The experimental results show that there is an obvious interface in the droplet, indicating that a droplet is composed of two incompatible parts, indicating that food-grade Janus droplets were successfully prepared based on the discrete phase separation between zein solution and sodium alginate solution and the structure of the microfluidic chip. Figure 7 The experimental results also show that the food-grade Janus droplet size is 9.27 μm and has a uniform particle size distribution, which is conducive to its subsequent application.

[0048] Experimental Example 5 Effect of Flow Rate on Food Grade Janus Particle Size Food-grade Janus droplets were constructed at different flow rates, and the particle sizes of food-grade Janus droplets were counted.

[0049] pass Figure 8 It can be seen from the experimental results that with the increase of flow rate, the particle size of food-grade Janus droplets decreases significantly, indicating that the particle size of food-grade Janus droplets can be well controlled by controlling the flow rate.

[0050] Experimental Example 6 Food Grade Janus Droplet Turbiscan Test A food-grade Janus droplet was placed in a sample vial and the Turbiscan Stability Index (TSI) of the droplet was measured. TSI is a parameter to measure the stability of a sample. The stability of a sample is inversely proportional to the TSI value. The better the sample stability, the smaller the TSI value. Fig. 9 It can be seen from the experimental results that the molecular weight of sodium alginate will affect the stability of food-grade Janus droplets, and food-grade Janus droplets constructed with smaller molecular weight have better stability.

[0051] Experimental Example 7 Thermal Stability of Food-Grade Janus Droplets The food-grade Janus droplets were heated at 50 °C for 30 min, and the structure of the food-grade Janus droplets was observed under a microscope.

[0052] pass Fig.10 It can be seen from the experimental results that the interface structure still exists in the droplets after heating, indicating that the droplets can still maintain the Janus structure, proving that food-grade Janus droplets have good thermal stability.

Claims

1. A food-grade Janus droplet with adjustable particle size constructed based on multiphase spatial recombination, characterized in that: The dispersed phases are zein solution and sodium alginate solution, and the emulsifier is dissolved in the oil phase as the continuous phase. Food-grade Janus droplets are prepared by controlling the spatial behaviors of the three phases.

2. A method for constructing food-grade Janus droplets with adjustable particle size based on multiphase spatial recombination, characterized in that: Based on mutually incompatible zein solution and sodium alginate solution as two dispersed phases, an emulsifier was dissolved in the oil phase as the continuous phase, and food-grade Janus droplets were prepared by controlling the spatial behaviors of the three phases.

3. The preparation method according to claim 2, characterized in that: The specific preparation method comprises the following steps: (1) dispersing sodium alginate in deionized water, stirring and dissolving, homogenizing, and adjusting the pH of the solution to obtain a sodium alginate solution as one of the dispersed phases; (2) dispersing zein in deionized water, stirring and dissolving, homogenizing, and adjusting the pH of the solution to obtain a zein solution as one of the dispersed phases; (3) dissolving the emulsifier in the oil phase to obtain a continuous phase solution; (4) The flow behaviors of zein solution, sodium alginate solution, and oil phase in the microfluidic chip were controlled separately to construct food-grade Janus droplets.

4. The preparation method according to claim 3, characterized in that include: The molecular weight of the sodium alginate in step (1) is 10-100 kDa.

5. The preparation method according to claim 3, characterized in that include: The sodium alginate concentration in the sodium alginate solution in step (1) is 1-5 wt %, and the solution pH is 11.5-12.

5.

6. The preparation method according to claim 3, characterized in that include: The zein concentration in the zein solution in step (2) is 6-15 wt %, and the solution pH is 11.5-12.

5.

7. The preparation method according to claim 3, characterized in that include: The homogenization method in steps (1) and (2) is selected from high-speed shearing, ultrasonic treatment and high-pressure homogenization.

8. The preparation method according to claim 3, characterized in that include: The emulsifier in step (3) is selected from one or more of polyglycerol ricinoleate (PGPR) and lecithin.

9. The preparation method according to claim 3, characterized in that include: The emulsifier concentration in step (3) is 1-3wt%.

10. The preparation method according to claim 3, characterized in that include: The oil in step (3) is selected from one or more of corn oil, soybean oil, peanut oil, medium-chain triglycerides and rapeseed oil.

Citation Information

Patent Citations

  • Fluoro-thiazolidone and synthetic method thereof

    CN117050031A

  • Preparation method of color-adjustable total internal reflection structural color liquid drops

    CN118271873A

Cited By

  • Method for constructing food-grade Janus nanoparticles based on thermodynamic equilibrium and instantaneous nano precipitation

    CN120753388A

  • Method for preparing food-grade Janus nanoparticles by ultrasonic-assisted induction of Maillard reaction

    CN120836725A